Kinerja Pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota - Rika Murdianingsih; Sulastri Sulastri; Rusdinal Rusdinal; Lusi Susanti (Journal of Educational Administration and Leadership, 2021)
Abstract The research is motivated by various problems that the authors encounter in the field which shows that the performance of employees is still not realized. The aspects studied were productivity, quality and timeliness. This research is quantitative in nature. The population in this study were al employess totaling 58 employess whose entire population was sampled. The data collection instrument was a questionnaire. The result is that the employess’s performance is in a good category.